Smartphone Usage Intensity and Its Relationship with Learning Interest Among Primary School Students - Prodyanatasari, Arshy (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
Smartphones have become an essential part of students’ lives, influencing their learning interest. This study examines the relationship between smartphone usage intensity and primary school students' learning interest using a quantitative survey approach. A total of 64 students from SDN Bandar Lor 1 Kota Kediri participated, with data analyzed using the Chi-Square test (χ² = 218.439, df = 30, p < 0.05). Findings show that higher smartphone usage is significantly linked to increased learning interest. 80% of students use smartphones for study-related searches, 75% for learning apps, and 70% for completing homework efficiently. Additionally, over 70% reported enhanced learning motivation. However, 77% also spend excessive time on smartphones, mainly for entertainment, leading to potential distractions and dependency. These results highlight that smartphones can be effective learning tools when used appropriately, but unregulated use may negatively impact focus. Guidance from parents and teachers is crucial to maximizing educational benefits while minimizing risks. This study is limited to a single school; future research should expand the sample size and explore long-term effects of smartphone use on cognitive and emotional development.